Evaluation Of Bronchodilator Use In Copd Patients Using The Atc/Ddd And Du90% Methods At Jember Paru Hospital - Ayu Putri MS; Adinda Safira (Indonesian Pharmacopeia Journal, 2026)
Bronchodilators are the primary therapy in the management of COPD; therefore, evaluating their use is crucial to ensure the rationality, safety, and effectiveness of treatment. This study aimed to evaluate bronchodilator use among hospitalized COPD patients at Jember Lung Hospital using the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) and Drug Utilization 90% (DU90%) methods. The study employed a non-experimental, quantitative observational design with a retrospective approach. Data were obtained from the medical records of hospitalized COPD patients at Jember Lung Hospital for the period of January–December 2025. The study population consisted of 170 patients, with a sample of 120 patients selected via purposive sampling based on inclusion criteria. Data were analyzed using univariate analysis. The results showed that the patient population was predominantly male (65%) and in the >66 age group (46.67%). Bronchodilators were most frequently administered via the inhalation route (56.84%), with Meprovent being the most commonly prescribed drug (47.54%), followed by Theobron (20.21%) and aminophylline (15.30%). Evaluation using the ATC/DDD method revealed that the Meprovent inhaler had the highest utilization rate, at 59.21 DDD/100 patient-days. Based on the DU90% analysis, the bronchodilators included in the DU90% segment were Meprovent inhaler, oral Theobron, and Farbivent inhaler, whereas intravenous aminophylline, oral Teosal, Spiriva inhaler, Combivent inhaler, and Spiolto inhaler fell into the DU10% segment. The study concludes that the Meprovent inhaler had the highest utilization rate; Meprovent inhaler, oral Theobron, and Farbivent inhaler showed high usage intensity among hospitalized COPD patients. Keywords: COPD, bronchodilator, ATC/DDD, DU90%, drug utilization evaluation.